Bases moleculares da resposta a estresses ambientais em vegetais: arroz, tomate e pêssego - Pegoraro, Camila (2012)
Abiotic stresses represent large threats to agriculture and food security, since they limit the productivity of the majority of cultivated plants. In order to identify the responses of plants to abiotic stresses and their associations with tolerance under different environmental conditions, concepts and techniques in molecular biology, cell biology and genetics have been used. The identification of genes responsive to stresses can be used to obtain plants tolerant to adverse environmental conditions by genetic transformation or directed crosses. Thus, this study had the objective the establishing of expression profiles of gene belonging to the ERF, HSP, HSF, TIM/TOM and TIC/TOC families in rice and tomato under low O2 stress. Also, the transcriptional profile of peaches under cold stress as obtained. The results indicate that in rice, some members of the ERF family present specific expression according to the stressing agent, while others have overlapping expression among different stresses. Besides, within the ERF family, some genes do present a complex regulation and others a simple regulation. In rice, some genes encode proteins belonging to the TIM/TOM and TIC/TOC complexes present high expression levels 24 hours after anoxia stress. However, after 72 hours under anoxia, the majority of genes were inhibited, suggesting an interruption on the transport of proteins to the mitochondria and chloroplast during the stress period. When the HSP expression profiles of flooding tolerant and sensitive rice cultivars were compared, transcript accumulation occurred for both cultivar types. However, the majority of genes evaluated were more responsive in the sensitive cultivar than in the tolerant, indicating that HSPs have an important association in the response to anoxia stress but are not directly involved in the tolerance. In tomato fruits stored under hypoxia, two sHSPs genes were highly induced by low oxygen levels, indicating a primary action of these genes on keeping cell homeostasis after the stress. In peaches, the application of gibberellic acid acts on preventing the damaged caused by cold by the induction of genes associated to lipid metabolism, cell wall degradation and trehalose synthesis.